Decorating an inadequate landscape : illustrating the acclimatisation of introduced bird species through wallpaper design : Master of Design thesis 2015 - Rogers, Ami (Massey University, 2015)
New Zealand has the second highest number of introduced bird species of any country (Troup, 2015). This is the result of acclimatisation societies introducing northern hemisphere birds to provide early settlers with European familarity, ease those afflicted with homesickness and ‘enrich’ the foreign landscape. Using archival research from the Nelson region, this project employs wallpaper pattern design to exhibit illustrations as a visual display of findings from the period of early introduced passerine bird acclimatisation. The design work functions as a metaphor for the ‘decoration’ of what was deemed an ‘inadequate landscape’, and a visual interpretation of written records from one chapter in New Zealand’s history.
Keywords: Wallpaper design; Introduced birds; Nelson; New Zealand